INTERRELIGIOUS EDUCATION MODEL IN SENIOR HIGH SCHOOL (SMA) BOPKRI 1 YOGYAKARTA - Khasan Bisri; Karwadi Karwadi (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
Abstract: Religious education at all levels of institutions are generally still dwelled on the perspective of the internal circle, intended for the internal, and less responsive to social changes. In other words, religious education is still monoreligious, so that institutions and religious communities are often stuttered toward the diversity and changes. In fact, the monoreligious model does not accept other people who are different. It does not foster a sensitivity on how to think, how to live and the needs of others who are a different religion. Such a model of religious education raises a wide impact on the mindset and attitude of religious students, one of which could potentially give rise to attitudes of intolerance. Therefore, it is necessary the presence of a renewal model of religious education that allows students to more insightful open to differences and diversity of religions. This research aims to know the implementation of the interreligious model in religious education at Senior High School (Sekolah Menengah Atas-SMA) BOPKRI 1 Yogyakarta. Data are collected by using interview, observation, and documentation, and verified by triangulation. The findings are that interreligious model at SMA BOPKRI 1 Yogyakarta has been implemented only on grade XII, whereas at the grades X and XI, the Christian religious education is applied. According to Michael Grimmit, the implementation of religious education at grades X and XI can be categorized as “learning religion", whereas in grade XII It can be categorized as “learning from religion”. On the other hand, by using the theory of Jack Seymour and Tabita Kartika, the model religious education in grades X and XI can be included as “in the wall”, whereas, in grade XII, it can be categorized as “beyond the wall”. Tolerance and multiculturalism insight of students of SMA BOPKRI 1 Yogyakarta by applying the interreligious model is already up on the fifth level of the multicultural barometer popularized by Karuna Center for Peacebuilding i.e. on the level of respect, recognizes, and contributes to other groups, or can be categorized at the highest level, namely the award on the similarities and differences, as well as celebrate plurality.